Detection of gram positive and gram negative organisms in sputum quality testing - Siti Syazwani, Razi (2012)
Sputum is a mucus that cough up from the lower airways which is a normal body fluid. The sputum consists of squamous epithelial cell, pus cells and bacteria. For this project, it only focus on bacteria organisms which is consists of two type of bacteria such as gram positive and gram negative bacteria. The purpose of this project is to detect and count the quantity for gram positive and gram negative bacteria. At the same time, the grading for both bacteria is identified based on grading criteria. Currently, gram positive and gram negative bacteria is detected and counted manually by human and the grading is identified. Since human might do some mistake in detection and summation for both bacteria and take a long time in doing this process, developing an automatic vision system is necessary to obtain more accurate results and time saving. This automatic vision system developed based on image processing technique which is involve of software simulation only by using MATLAB simulation. In developing this project, some techniques of the image processing is applied into MATLAB simulation such as image analysis, image segmentation, image enhancement, morphological process and other. Then, the results for summation and grading are displayed on MATLAB Graphical user Interface (GUI). Last but not least, the result for grading obtained give similar value compare to validation test from HUSM.